P326 The effect of compliance during exclusive enteral nutrition on faecal calprotectin levels in children with Crohn's disease. (21st January 2022) - Mckirdy, S; Russell, R; Hansen, R; Svolos, V; Gkikas, K; Logan, M; Gerasimidis, K
Abstract: Background: It is yet unclear whether suboptimal response to exclusive enteral nutrition (EEN), in some children with Crohn's disease (CD), is explained by poor compliance. All proprietary feeds used for EEN are gluten-free; hence patients' compliance to EEN could be determined by detecting gluten immunogenic peptide (GIP), a biomarker of gluten intake, in faeces. Methods: The concentration of GIP was measured in the faeces of, 45 children (3–17 years) with CD prior to and during (33 &, 54 days) treatment with EEN. Associations with GIP and faecal calprotectin (FCAL) levels were explored at, 33 and, 54 days of EEN. Results: GIP was present in, 37 of the, 40 (93%) patients who provided stool samples prior to starting EEN, indicating typical gluten consumption in CD patients. In patients with undetectable GIP at both, 33 and, 54 days of EEN, FCAL significantly decreased from baseline (mean decrease, 33 days: -743mg/kg, 54 days: -1043mg/kg, p<0.001), but not in patients who had detectable GIP. At EEN completion, patients with undetectable GIP had a lower FCAL by, 763mg/kg than patients with a positive GIP result (p=0.041) and demonstrated a greater decline from baseline FCAL (-69% vs +5.%, p=0.021). Conclusion: Poor response to EEN might be explained at least in part by diminished compliance and dietary transgressions. Faecal GIP might be useful as a proxy biomarker of EEN compliance.